Seizure semiology reflects spread from frontal to temporal lobe: evolution of hyperkinetic to automotor seizures as documented by invasive EEG video recordings - AĞAN YILDIRIM, KADRİYE (JOHN LIBBEY EUROTEXT LTD, 2013)
This patient report demonstrates the importance of seizure evolution in the localising value of seizure semiology. Spread of epileptic activity from frontal to temporal lobe, as demonstrated by invasive recordings, was reflected by change from hyperkinetic movements to arrest of activity with mild oral and manual automatisms.
Keywords: hyperkinetic seizure; hypermotor seizure; automotor seizure; seizure semiology; temporal lobe epilepsy; frontal lobe epilepsy; FOCAL EPILEPSIES; LOCALIZING VALUE; CLASSIFICATION; TERMINOLOGY